2011
DOI: 10.1177/000313481107701002
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Serum Albumin but Not Prealbumin Is an Excellent Predictor of Postoperative Complications and Mortality in Patients with Gastrointestinal Cancer

Abstract: Preoperative serum albumin level is well recognized as a general predictor of adverse surgical outcomes in patients with gastrointestinal (GI) malignancy. Whether serum albumin or prealbumin levels can better predict postoperative surgical complications and death remains unknown. A retrospective review of 641 consecutive patients operated nonemergently for GI malignancies between January 1, 1997, and July 31, 2008, disclosed that 104 patients (16.2%) had complications and 23 (3.6%) subsequently died. All 641 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 11 publications
5
25
1
Order By: Relevance
“…Whether the serum PAB concentration is a more accurate indicator of nutritional status and an independent mortality predictor compared to previous markers, i.e., albumin and BMI, has been a matter of debate. This controversy persists with respect to the general population [27][28][29] and patients with various conditions [26,[30][31][32]. In present study, when other nutritional markers (albumin, cholesterol, and BMI) were included into Cox regression models, no difference was found in the association between serum PAB and overall mortality.…”
Section: Discussionmentioning
confidence: 62%
“…Whether the serum PAB concentration is a more accurate indicator of nutritional status and an independent mortality predictor compared to previous markers, i.e., albumin and BMI, has been a matter of debate. This controversy persists with respect to the general population [27][28][29] and patients with various conditions [26,[30][31][32]. In present study, when other nutritional markers (albumin, cholesterol, and BMI) were included into Cox regression models, no difference was found in the association between serum PAB and overall mortality.…”
Section: Discussionmentioning
confidence: 62%
“…In patients with chronic hemodialysis, for instance, numerous studies have shown that lower prealbumin levels are independently associated with morbidity and mortality, independent of serum albumin level or other clinical risk factors . On the other hand, several other studies have argued that albumin is the key marker for mortality, rather than prealbumin . As first reported in a 1936 study of patients undergoing ulcer surgery, malnutrition affects outcomes in surgical patients .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, metastatic tumor cells induce Kupffer cells in the liver to produce cytokines, and reduce albumin synthesis (29). Consequential hypoalbuminemia is also correlated with impairment of a variety of immune system functions (30), and helps tumor cell promotion and metastasis as a result.…”
Section: Discussionmentioning
confidence: 99%